2007
DOI: 10.1002/hyp.6783
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐storm evaporation as a component of canopy interception loss in dryland shrubs: observations from Fowlers Gap, Australia

Abstract: Abstract:Interception losses from the canopies of dryland plant taxa remain poorly understood, especially the relative contributions of intra-storm and post-storm evaporative losses. Employing a new measuring apparatus, this study uses low-intensity simulated rain, matched to the properties of local rain, to explore interception processes in bluebush shrubs at an Australian dryland site. Five shrub specimens were exposed to simulated rain for 60-90 min. Experiments were repeated at three rainfall intensities (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 41 publications
(47 reference statements)
1
49
0
Order By: Relevance
“…The percentage of event rainfall captured by vegetation and associated ground cover generally decreases as rainfall intensity increases (Carlyle-Moses, 2004;Owens, Lyons, & Alejandro, 2006). For low-intensity, short-duration rainfall events, most of the precipitation is captured by plant canopies, litter, and other ground cover and is lost to evaporation (Dunkerley, 2008;Owens et al, 2006). Water input during highintensity or prolonged rainfall events usually exceeds interception storage capacity, resulting in delivery of water to the ground surface via throughflow and stemflow (Carlyle-Moses, 2004; D. Dunkerley, 2000;D.L.…”
Section: Vegetation Effects On Water Input and Runoff Generationmentioning
confidence: 98%
“…The percentage of event rainfall captured by vegetation and associated ground cover generally decreases as rainfall intensity increases (Carlyle-Moses, 2004;Owens, Lyons, & Alejandro, 2006). For low-intensity, short-duration rainfall events, most of the precipitation is captured by plant canopies, litter, and other ground cover and is lost to evaporation (Dunkerley, 2008;Owens et al, 2006). Water input during highintensity or prolonged rainfall events usually exceeds interception storage capacity, resulting in delivery of water to the ground surface via throughflow and stemflow (Carlyle-Moses, 2004; D. Dunkerley, 2000;D.L.…”
Section: Vegetation Effects On Water Input and Runoff Generationmentioning
confidence: 98%
“…The degradation is typically characterised by a loss of perennial plant cover (Whisenant, 2002), which increases the amount and connectivity of bare ground. This leads to soil crusting and compaction, a decline in water infiltration and increased runoff (du Toit et al, 2009;Mills and Fey, 2004;Snyman and du Preez, 2005). Furthermore, higher temperatures of the exposed soil (Rietkerk et al, 2000;Snyman and du Preez, 2005) accelerate the evaporative loss of soil water.…”
Section: Introductionmentioning
confidence: 97%
“…Along with the size and intensity of rainfall events, the fate of rainwater is also influenced by the weather conditions during and after rainfall events (Dunkerley, 2008;Loik et al, 2004). Winter rainfall is produced by low pressure systems resulting in chilly and windy weather for several days (Desmet and Cowling, 1999), which may influence the mechanisms by which rehabilitation treatments affect soil water status.…”
Section: Introductionmentioning
confidence: 99%
“…Studies looking in detail into individual rainfall event characteristics in RCM simulations are missing despite the fact that such characteristics of heavy rainfall events as event depth, duration, or intensity are relevant for urban hydrology (e.g. Einfalt et al, 1998;Barbosa et al, 2012;Willems et al, 2012) and determine characteristics of various hydrological processes as overland flow generation and shape of the resulting hydrograph (Singh, 1997), soil moisture dynamics (Wang et al, 2008;He et al, 2012), infiltration (Ran et al, 2012), rainfall erosion (Wischmeier and Smith, 1978), evaporation (Dunkerley, 2008a), storm sewer flow rates and direct runoff (Schilling, 1991;Giulianelli et al, 2006). Therefore considering these individual rainfall event characteristics is important also in RCM evaluation studies, which has been highlighted already by, for example, Westra et al (2014), who suggested (among other things) to focus on (spatial structure and) temporal evolution of rainfall events and their timing and intermittency.…”
Section: Introductionmentioning
confidence: 99%